Sosialisasi Hukum, Keselamatan, Dan Keamanan Serta Keberadaan Anjungan Fasilitas Operasi Minyak Dan Gas Bumi (Kasus pada Nelayan di Pesisir Pantai Utara Jawa Barat) - S.E. Friska Sirait; Nurmala Katrina Pandjaitan; Krishnarini Matindas (Jurnal Komunikasi Pembangunan, 2016)
In case of oil and natural gas production, a restricted zone within 500-meter-wide around offshore platform was established. The restricted zone was established to protect all activities in the sea, including fishing. Socialization on law, safety, and security, and the existence of oil and gas operational facility platform has been held. Yet, it hasn’t stopped the fishers’ effort to do fishing in the restricted zone. Therefore, this study tries to analyze communication model in the socialization and components that affect communication as well as correlation among the factors that influence the effectiveness of communication and fishers' obedience toward prohibition of entering the restricted zone. The study was conducted in one of the coastal villages in Karawang Regency, West Java. Data were collected by using questionnaire, which was supported by conducting qualitative method. The data, which were analyzed by rank Spearman Correlation Test. Results showed that communication model on socialization is not a convergent model but a linear and interactional model. There was a difference between a facilitator of socialization and fishing communities in terms of education level, social class, and language that becomes an obstacle for fishers to communicate. The message materials have not been complete yet, and there is no emotional and fear approachesin the message content of socialization. The use of radio as a communication channel has been ineffective because most fishers do not have a radio. Experience as fishers is significantly related to the fishers’ obedience and their view is very significant to their obedience. Meanwhile, the age, educational level, use of fishing tools, attendance at faceto-face socialization, exposure on advertising spots in radio and posters at Fish Auction Site (TPI), and the frequency of communication among the fishers are not significantly related to fishers’ obedience toward the prohibition of entering the restricted zone.Keywords: socialization, restricted zone, and fishers’ obedience